The romance of heroism and heroic leadership - Goethals, George R.; Allison, Scott T. (Emerald Publishing Limited, 2019)
Heroes permeate our culture. From superheroes on screen to the everyday heroics of our public services, the word 'hero' is a familiar descriptor in every form of media. But what makes a hero? And what makes heroes 'heroic'? Leadership experts George R. Goethals and Scott T. Allison explore how the romantic conceptions of heroes and heroic leaders are constructed, both in real life and in our heads. Looking at the dichotomy of heroism and villainy, they offer insights into Donald Trump's ascension to the US presidency, particularly detailing the correspondence between the needs of the US public and the promises the former reality TV star made in reply. They also consider how three highly charismatic men dramatically and fundamentally changed American society in the mid-twentieth century - Martin Luther King (1929-1968), Elvis Presley (1935-1977), and Muhammad Ali (1942-2016), called here the "Three Kings" of the US. This exciting and innovative study explores how charisma and human needs create images of individuals as heroes and villains. For researchers and students of psychology and leadership, this is a fundamental text on the creation of both genuine heroes, and false idols.
Keywords: Leadership -- Psychological aspects.; Heroes -- Psychological aspects.; Business & Economics -- Leadership.; Management: leadership & motivation.; elektronické knihy; electronic books